Insights into the structure of MoS2/WS2 nanomaterial catalysts as revealed by aberration corrected STEM - Deepak, Francis Leonard; Esparza, Rodrigo; Castro Guerrero, Carlos Fernando; Mejía Rosales, Sergio; López Lozano, Xochitl; Yacamán, Miguel José (2012)
Molybdenum disulfide/Tungsten disulphide (MoS2/WS2) is a compound very useful for its properties; it is used as lubricant, catalyst in hydrodesulfuration, in hydrogen fuel storage, etc. As part of the 2nd Joint Congress of the Portuguese and Spanish Microscopy Societies the present work reports about the different types of MoS2/WS2 nanomaterials which have been investigated by using aberration corrected STEM namely: (1) MoS2 nanotubes (2) MoS2 hexagonal nanoplates, (3) rippled or helical MoS2 nanowires, (4) Co-doped MoS2/WS2 nanowires and (5) fullerene-like WS2 nanoparticles